2016
DOI: 10.1111/jsap.12526
|View full text |Cite
|
Sign up to set email alerts
|

Owners’ attitudes and practices regarding nutrition of dogs diagnosed with cancer presenting at a referral oncology service in Ontario, Canada

Abstract: Following a cancer diagnosis, dog owners appear to change their approach to managing their dog's nutrition. Given the value owners place on veterinary nutritional advice, veterinarians have a key role in guiding nutritional management of the canine cancer patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 40 publications
6
35
3
Order By: Relevance
“…Nevertheless, the majority of respondents reported trusting veterinarians either “very much” or “somewhat” with respect to pet nutrition. These data are similar to previous studies, which have reported that most veterinarians do not discuss nutrition with clients at each veterinary visit or that, while veterinarians are considered trusted resources, with respect to pet nutrition, they are often not consulted (Connolly, Heinze & Freeman, 2014; Rajagopaul et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, the majority of respondents reported trusting veterinarians either “very much” or “somewhat” with respect to pet nutrition. These data are similar to previous studies, which have reported that most veterinarians do not discuss nutrition with clients at each veterinary visit or that, while veterinarians are considered trusted resources, with respect to pet nutrition, they are often not consulted (Connolly, Heinze & Freeman, 2014; Rajagopaul et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…A majority of pet owners reported that they trust veterinarians as a knowledgeable resource with respect to pet nutrition either “very much” or “somewhat.” Most pet owners feeding RAP reported trusting veterinarians either “not very much” or “a little” with respect to pet nutrition. Similarly, previous studies have reported that pet owners that do not feed commercial diets have less trust in veterinarians, as a source of information on pet nutrition, than those that feed commercial diets (Connolly, Heinze & Freeman, 2014; Rajagopaul et al, 2016). Prior studies have reported that clients consider veterinarians to be their principle or most trustworthy source of information regarding pet nutrition (Connolly, Heinze & Freeman, 2014; Freeman, Janecko & Weese, 2013; Kienzle, Bergler & Mandernach, 1998; Laflamme et al, 2008; Rajagopaul et al, 2016), however only 9% of RAP feeders in this study reported that a veterinarian or animal nutritionist was their primary resource regarding their pet’s nutrition.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…5 Certain components of the diet and the diet type itself may be called into question for its nutritional adequacy, leading about 80% of owners to believe a diet change for their dog may be needed post-diagnosis; such as inclusion of homemade cooked or raw dietary components, and exclusion of conventional dry or wet dietary components. 5 This is a concern, as homemade diets are often deficient in some essential nutrients, [6][7][8] and raw diets possess risk of bacterial contamination. [9][10][11][12] Therefore, it is important to monitor dietary decisions made by owners of dogs with cancer to target nutrition education and how clinicians can best advise clients following a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%